USULAN STRATEGI PERUSAHAAN DENGAN MENGGUNAKAN METODE QSPM: STUDI KASUS PADA PERUSAHAAN DAUR ULANG LIMBAH TEKSTIL DI BANDUNG - Audy Tanhati (Center for Economic Studies Universitas Katolik Parahyangan, 2015)
In the era of increased competition, a company has to compete with others to achieve higher earnings capacity. Many ways have been done to make sure their cashflow balance. Some companies focus on their earnings rather than other aspects. Marketing is the main concern to maintain the existence of the company. Some of them were succeed and the others were failed due to lack of good strategy and plan. This article explains about how to develop a company’s strategy using Quantitive Strategy Method. This method need a deep analysis about internal and external environment of the company to comprehend the strengths, weaknesses, oppprtunities and threats (SWOT). Some of the steps in this method will be discussed using a textile company in Bandung as an example. Keywords: Company’s strategy, quantitive strategy, internal environment, external environment, SWOT.